The Influence of Quality of Work Life, Work Life Balance, And Financial Reward on Employee Job Satisfaction (Case Study at PT. Nayfisha Bintang Jaya) - Jannah, Shofi Nur; Indiworo, Hawik Ervina; Akbar, Shofif Sobaruddin (Bina Bangsa International Journal of Business and Management, 2025)
The purpose of this study is to analyze the influence of Quality of Work Life (X1), Work Life Balance (X2), and Financial Reward (X3) on employee job satisfaction (Y). The data in this study were collected using a questionnaire method administered to 60 respondents to determine their responses to each variable. The data were analyzed using quantitative analysis. The analytical technique employed in this study is multiple linear regression analysis to test the research hypotheses. Based on the results, it is concluded that Quality of Work Life has a significant effect on employee job satisfaction; Work Life Balance has a significant effect on employee job satisfaction; and Financial Reward has a significant effect on employee job satisfaction. Simultaneously, Quality of Work Life, Work Life Balance, and Financial Reward significantly affect employee job satisfaction. The coefficient of determination test shows that job satisfaction is influenced by these three variables by 42.1%, while the remaining 57.9% is influenced by other factors not included in this study.